2023
DOI: 10.24875/gmm.m20000331
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the low-density lipoprotein (LDL)/high-density lipoprotein (HDL) index with antioxidant enzymes and with the oxLDL/HDL index

Abstract: Introduction:The low-density lipoprotein (LDL)/high-density lipoprotein (HDL) index is a predictive factor for atherosclerosis, which is associated with oxidative modifications. Objective: To assess the association of the index with oxidative stress markers. Methods: 444 subjects were included and were clinically, anthropometrically and biochemically characterized; superoxide dismutase, glutathione peroxidase 3 (GPx3), magnesium and oxidized LDL (oxLDL) index (oxLDL/HDL) were quantified. Results: A decrease of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The results of some studies showed that, in magnesium deficiency, serum HDL-C levels were significantly lower and TG levels were significantly higher [ 55 – 57 ]. Magnesium intake may likely contribute to increasing lipoprotein lipase activity [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies showed that, in magnesium deficiency, serum HDL-C levels were significantly lower and TG levels were significantly higher [ 55 – 57 ]. Magnesium intake may likely contribute to increasing lipoprotein lipase activity [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism between the LDL/HDL ratio and long-term coronary revascularization in STEMI patients has not been elucidated. Previous studies have confirmed that the occurrence of adverse cardiovascular events, including coronary revascularization, is related to biomarkers such as myeloperoxidase (MPO), glutathione peroxidase, and gamma-glutamyl transferase (GGT), which can reflect the level of human oxidation reaction (13)(14)(15), and the LDL/HDL ratio can also reflect the level of oxidation reaction (6). Therefore, we speculate that the LDL/HDL ratio can reflect the level of oxidation reactions to predict the long-term risk of coronary revascularization in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), including superoxide anions (O 2 -) and hydroxyl radicals (-OH), etc., are oxygen single-electron reduction products produced in enzymatic reactions catalyzed by enzymes such as cyclooxygenase and peroxidase (16). LDL generates oxidized low-density lipoprotein (ox-LDL) through the action of ROS, and ox-LDL can form foam cells after being engulfed by represents antioxidant levels of the human body, will increase by 1 U/mL; when the LDL/HDL ratio decreases by 0.023, the glutathione peroxidase (GPx3), which also represents antioxidant levels of the human body, will increase by 1 nmol/min/mL (6). Therefore, the LDL/HDL ratio can represent the level of human oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation